The Impact of the COVID-19 Pandemic on Work Productivity in Project X in Batam Using the Data Envelopment Analysis (DEA) Method - Br Sembiring, Yohana Selliabreint; Wiguna, Putu Artama (Journal of Applied Sciences, Management and Engineering Technology, 2024)
The development of 4.0 industry has a major influence on worldwide gas consumption. In order to meet the requirement, the gas producing company, such as Qatargas, performs expansion by building more offshore platforms on the fields. Qatargas’s infrastructure contructs by Project X that operating in Batam, Indonesia. The project X awarded by Qatargas to commence by the end of 2021. The scope of work includes engineering, procurement, construction, and installation (EPCI). During the construction, an unexpected even, COVID-19, occurred and caused a negative impact to the construction productivity. A non-parametric Data Envelopment Analysis (DEA) is utilized to measure performance trends with focus on project X daily progressing report from 2022 (during pandemic) until 2023 (post-pandemic). SWOT and PEST are utilised to analyse the improvement strategy by Project X. Efficiency measurement by DEA has 3 different variable, such as total employee, total welding made, and work pack issued, whereby the output is total manhours earned. This report also analyses six division of Decision-Making Unit (DMU). The research employs SWOT analysis to identify factors affecting project performance and strategies for efficiency improvement. Based on the analysis, there is no significant impact due to pandemic since PT X still could continue to perform fabrication while maintaining the required health protocol. The mean efficiency is 0,734 in 2022 and 0,656 in 2023. The project productivity declines by 0,078 because of declining efficiency parameter on Production Electrical dan Structural Quality Division. The efficiency improvement strategy for Project X includes optimizing the number of employees, minimizing rework, and daily monitoring of manhours earned to prevent inaccurate work hour claims.